Using recycled aggregate for seismically monitoring of embankment-subsoil model. (December 2021) - Guo, Lijie; Li, Wenchen; Namdar, Abdoullah
Highlights: The recycled aggregate was used for seismic modeling of embankment-subsoil. The mechanical properties and interaction of the recycle aggregate control strain and stress directions. The modulus elasticity of the model was improved and lateral displacement of the model was minimized. The suggested method improves the seismic stability of the embankment-subsoil model. The statistical analysis was used for verification numerical simulation. Abstract: Huge volume of recycled aggregates are produced annually, in the economic and environmental view, they need to consume in the appropriate section of the construction industry. In this paper, a recycled aggregate has been used for seismic modeling of embankment-subsoil. The nonlinear software was employed in the modeling. For assessment modulus elasticity and lateral displacement of the model, the mechanical properties of the soil and the recycle aggregates designing have been selected as parameters. Three models, with the same geometry and different type of materials, have been configured. Results revealed the recycle aggregate enhances seismic mitigation of the model. The outcome of this study demonstrated using recycled aggregate in the construction industry impacts on ( i ) control strain and stress directions, ( ii ) minimize lateral displacement of the model, ( iii ) enhance modulus elasticity of the embankment-subsoil model, and ( iv ) the seismic stability of the embankment-subsoil model. The statistical analysis showed, the high accuracy for interpreting modulus elasticity of the model, and it is good evidence for numerical analysis accuracy results.